The age of the strongman how the cult of the leader threatens democracy around the world - Rachman, Gideon (New York Other Press, 2022)
The author of Easternization, an award-winning journalist, offers an intimate look at the rise of strongman leaders around the globe, charting the most urgent political story of our era. We are in a new era: authoritarian leaders have become a central feature of global politics. Since 2000, self-styled strongmen have risen to power in capitals as diverse as Moscow, Beijing, Delhi, Brasilia, Budapest, Ankara, Riyadh and Washington. These leaders are nationalists and social conservatives, with little tolerance for minorities, dissent or the interests of foreigners. At home, they claim to be standing up for ordinary people against globalist elites; abroad, they posture as the embodiments of their nations. And everywhere they go, they encourage a cult of personality. What's more, these leaders are not just operating in authoritarian political systems but have begun to emerge in the heartlands of liberal democracy. From Trump, Putin and Bolsonaro to Erdogan, Xi and Modi, Gideon Rachman pays full attention to the strongman phenomenon around the world and uncovers the complex and often surprising interaction between these leaders. In the process, he finds the common themes in our local nightmares and offers a bold new paradigm for understanding our world, and finds global coherence in the chaos of the new nationalism, leadership cults and hostility to liberal democracy. While others have tried to understand the emergence of these new leaders individually, Age of the Strongman provides the first truly global treatment of the new nationalism, underpinned by an exceptional level of access to key actors in this drama: Gideon Rachman has been in the same room with most of these strongmen and reported from their countries over a long journalistic career.
Includes index
Keywords: Authoritarianism